The Relationship Between Nutritional Status and Sexual Maturity of Students at Al-Irsyad Al-Islamiyyah II Elementary School, Bekasi - Salsabila Putri Anandita; Sri Hastuti Andayani; Tuty Herawaty (Jurnal Indonesia Sosial Sains, 2026)
Puberty is a transitional period to adulthood characterized by physical, cognitive, and psychosocial changes. One of the indicators is sexual maturity and reproductive ability, which are influenced by various factors, including nutritional status. Nutritional imbalances can accelerate or delay sexual maturity. This study aims to determine the relationship between nutritional status and sexual maturity in students of SD Al-Irsyad Al-Islamiyyah II Bekasi. The design of this study is quantitative, with an analytical descriptive approach using a cross-sectional method. The sample consisted of 60 students in grades 4, 5, and 6, obtained using a total sampling technique. Nutritional status was measured using the Body Mass Index (BMI) based on the CDC 2000 growth chart, while sexual maturity was assessed using the Tanner staging questionnaire. The data were analyzed using the Chi-square test and Fisher’s exact test. The results showed a significant relationship between nutritional status and sexual maturity in male students, with a p-value = 0.023, and a p-value = 0.036 in the female group. Both results indicate that there is a significant relationship between nutritional status and sexual maturity in boys and girls.